Efficacy of Combination of Ketamine and Morphine for Intravenous Patient Controlled- Analgesia in Upper Abdominal Surgery at Srinagarind Hospital - Ratanasuwan, Panaratana; Nonphiaraj, Saranyoo; Pongjanyakul, Sasiwimon; Somdee, Wilawan; Taesiri, Worranut (Srinagarind Medical Journal, 2015)
Background and objective: Most of upper abdomen postoperative pain is severe. Control pain has many methods. Up to date, morphine is the main analgesic drug which has many uncomfortable side effects due to nausea, vomiting, sedation and respiratory depression. Reducing morphine consumption may benefit for patients well being. Ketamine is one of analgesic drug which inhibit NMDA receptor. Therefore, this study aims to investigate the efficacy of the combination of ketamine and morphine in the upper abdominal postoperative pain. Material and Method: Informed consents patients were double blind randomized into two groups; i) M group received morphine 1mg/ml, and ii) MK group received ketamine 1 mg plus morphine 1 mg /ml of intravenous patient-controlled analgesia (IV-PCA) after finished the operation. All pateints were assessed the postoperative morphine consumption, numerical rating score (NRS) of pain and side effects (sedative score, nausea, vomiting, urinary retention, pruritus, hallucination, and nightmares) at recovery room and every 4 hours until 48 hours. Results: Sixty-seven patients completed the study. Postoperative morphine consumption at recovery room , 24 and 48 hours were significant lower in MK group (n=34) by 6.13±2.64, 27.91±11.1, 18.53±9.76 mg compared to M group (n=33) by 8.1±3.55, 43.24±15.32, 28.09±9.12 mg, respectively ( p<0.001). NRS was similar between the two groups. No difference side effects were observed in both groups. Conclusion: Combination of ketamine and morphine via IV PCA is effective to control upper abdominal postoperative pain.